(4x+5)=3(x+5)

Simple and best practice solution for (4x+5)=3(x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4x+5)=3(x+5) equation:



(4x+5)=3(x+5)
We move all terms to the left:
(4x+5)-(3(x+5))=0
We get rid of parentheses
4x-(3(x+5))+5=0
We calculate terms in parentheses: -(3(x+5)), so:
3(x+5)
We multiply parentheses
3x+15
Back to the equation:
-(3x+15)
We get rid of parentheses
4x-3x-15+5=0
We add all the numbers together, and all the variables
x-10=0
We move all terms containing x to the left, all other terms to the right
x=10

See similar equations:

| 13+7=8x+27 | | 4c-22=34 | | 4(3x5)=6x-2 | | 3=j/3-4 | | -6|h-4|=-24 | | 10+3r=16 | | -7d-3=10d-6 | | 5(y-94)=15 | | 5x-17=-2x^ | | 7(1d-2)-3d=5-2(d+3)+4d | | 5(y−94)=15 | | -11+-2=-20-10t | | 5x-17=-2x | | v/4+11=18 | | 10z+20=60 | | 6x+3+2x=-13 | | 3(2x+3)-2=(X-2) | | 1/2(6b-8)=1b | | 1/y-4+2/y+3=10/y^2-y-12 | | 6(b-88)=12 | | 14+2x=-6-3x. | | -24.26674+0.6a=3.6a-0.28a | | x/4=x-9/3 | | p/4+10=11 | | 13+16+18j=19j+10 | | 6^-2m=216 | | 94x+1/2x=44 | | 8(x-10)+2(×+60)=0 | | 13=16+18j=19j+10 | | 8u-28=28 | | 3w-17=22 | | -2x-14=6x+4 |

Equations solver categories